2001
DOI: 10.1021/om000972f
|View full text |Cite
|
Sign up to set email alerts
|

CH Bond Activation in Cations of the Type {[(2,4,6-Me3C6H2NCH2CH2)2NMe]ZrR}+ and a Simple Solution that Yields a Catalyst for the Living Polymerization of 1-Hexene

Abstract: {[(MesNCH 2 CH 2 ) 2 NMe]ZrMe}[B(C 6 F 5 ) 4 ] and intermediates in the polymerization reaction of 1-hexene that are formed from it decompose as a consequence of CH activation in an ortho methyl group in the mesityl substituent. The intermediates in the polymerization reaction decompose significantly more readily than does {[(MesNCH 2 CH 2 ) 2 NMe]ZrMe}[B(C 6 F 5 ) 4 ]. On the other hand, analogous cationic complexes that contain the [(2,6-Cl 2 C 6 H 3 NCH 2 CH 2 ) 2 NMe] 2ligand are relatively stable and will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 24 publications
4
46
0
1
Order By: Relevance
“…A similar decomposition pathway of a cationic zirconium complex through CH bond activation of an adjacent methyl group had previously been uncovered by Horton and co‐workers in a structurally related triamido system 108. A simple change in aryl substitution from 2,4,6‐trimethylphenyl to 2,6‐dichlorophenyl prevented CH activation of the ligand, and a living 1‐hexene polymerization catalyst precursor 29 b was obtained 103. The polymer generated with catalyst 29 b /[Ph 3 C][B(C 6 F 5 ) 4 ] at 0 °C was of higher molecular weight than that produced with the NON catalysts 28 ( M n up to 79 000 g mol −1 ), while the molecular weight distribution of the polymer remained extremely narrow ( M w / M n , 1.01–1.04).…”
Section: Titanium Zirconium and Hafnium Catalysts For Living Alksupporting
confidence: 60%
See 1 more Smart Citation
“…A similar decomposition pathway of a cationic zirconium complex through CH bond activation of an adjacent methyl group had previously been uncovered by Horton and co‐workers in a structurally related triamido system 108. A simple change in aryl substitution from 2,4,6‐trimethylphenyl to 2,6‐dichlorophenyl prevented CH activation of the ligand, and a living 1‐hexene polymerization catalyst precursor 29 b was obtained 103. The polymer generated with catalyst 29 b /[Ph 3 C][B(C 6 F 5 ) 4 ] at 0 °C was of higher molecular weight than that produced with the NON catalysts 28 ( M n up to 79 000 g mol −1 ), while the molecular weight distribution of the polymer remained extremely narrow ( M w / M n , 1.01–1.04).…”
Section: Titanium Zirconium and Hafnium Catalysts For Living Alksupporting
confidence: 60%
“…Activation of 29 a with [Ph 3 C][B(C 6 F 5 ) 4 ] and subsequent reaction with 1‐hexene led to the formation of poly(1‐hexene) which displayed limited average molecular weight and broader molecular weight distribution than the polymer obtained with the NON system 28 . Subsequent studies revealed that this non‐living behavior was caused by catalyst decomposition by CH activation of one of the mesityl o ‐methyl substituents, producing a dimeric decomposition product that was characterized by X‐ray crystallography (Scheme ) 103. A similar decomposition pathway of a cationic zirconium complex through CH bond activation of an adjacent methyl group had previously been uncovered by Horton and co‐workers in a structurally related triamido system 108.…”
Section: Titanium Zirconium and Hafnium Catalysts For Living Alkmentioning
confidence: 65%
“…[ 3 verhinderte Ket-ten¸bertragungen und f¸hrte zu einer lebenden Polymerisation von 1-Hexen und hˆheren a-Olefinen (Schema 16). [103] Eine ‰hnliche Zersetzung 4 ] 31 (R Et, nBu, iBu, nPr, iPr). In CH 2 Cl 2 als Lˆsungsmittel war die katalytische Aktivit‰t drastisch hˆher, und es wurden hochmolekulare ataktische Polymere (M n > 120 000 g mol À1 ) mit engen Molekulargewichtsverteilungen (M w /M n 1.07) erhalten.…”
Section: Metallocenkomplexeunclassified
“…Indeed, cationic complexes containing the ligand set (2,6-Cl 2 C 6 H 3 NCH 2 CH 2 ) 2 NMe] 2À were found to be fairly stable (e.g., hours at 0 1C), and polymerized 1-hexene in a living manner (0 1C, chlorobenzene). [72][73][74] Asymmetric variations of this type of diamide N-donor ligand set have been synthesized (see XXVIII, Fig. 48, left), which contained ethylene/o-phenylene arms.…”
Section: Complexes Based On Non Ligandsmentioning
confidence: 99%